Assuring Quality in Teacher Education: Some Emerging Concerns, Issues & Future Directions in the present Changing Knowledge Era - SAIF, SHAZLI (IJRDO- Journal of Educational Research, 2019)
There is a growing concern of assuring quality at all levels of education in the present educational scenario. The quality of education we provide to our children depends on the quality of education of teacher we inject into the education system, which in turn depends on the quality of teacher education programme. Quality is not just the quantum of knowledge imparted to students but also the effectiveness with which they are able to apply that knowledge in meeting the challenges of tomorrow. Quality in teacher education programme also depends on the quality of teaching. For this there is an urgent review of curriculum of teacher education programme. The quality of pre-service and in-service education needs to be upgraded. It has been rightly said by the Education Commission (1964-66) that, “ Of all the different factors which influence the quality of education and its contribution to national development, the quality, competence and character of teachers are undoubtedly the most significant”. Since the dawn of independence, the Indian teacher education has undergone drastic changes. The major observable change is the mushrooming of educational institutions. Though, these are in compliance with growing needs of increasing student enrolment and student graduates, these institutions, especially self-financing ones, lack the true spirit of education that is development of individual work. Thus, quantity is overpowering quality. Quality of education and especially, teacher education has deteriorated to an alarming extent. The present paper discusses the need of teacher education programs to be innovative and various practices that can be included. It has been recognized that the present teacher education program should be structured and modified in a way that enables them to respond dynamically to the new problems and challenges in the field of education, then only teacher can help in national development. The present paper also highlights the need of quality, quality control, quality assurance, and assessment of quality, quality concerns and the steps which are to be taken for maintaining quality standards.